Stability analysis in blond psyllium (Plantago ovata) - Godawat, S L; Sharma, A K; Bordia, P C (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the winter season of 1992-93 amI 1993-94 to study stability in 12 promising genotypes('R149', 'R1 87', 'R1 88', 'R1 89', 'MSB 2', 'MSB 4', 'MSB 6', 'MSB 8', 'Sel 10', 'G12', 'H12' and' H15') of blond psyllium[Plantago ovata Forsskal) under 4 different environments. Variance due to genotypes, environments, genotypes X environmentinteraction and its linear and non-linear components were found significant for spikes/plant alld seed yield. The genotypes'R189' and 'GI 2' had high mean, regression coefficient around 1 and non-significant deviation from regression for seedyield. These genotypes were found suitable in different agro-climatic conditions of Mandor and Udaipur in Rajasthan.